Feasibility of Round Window Stimulation by a Novel Electromagnetic Microactuator. (29th October 2017) - van Drunen, Wouter Johannes; Mueller, Mathias; Glukhovskoy, Anatoly; Salcher, Rolf; Wurz, Marc Christopher; Lenarz, Thomas; Maier, Hannes
Abstract : Introduction . Most implantable hearing aids currently available were developed to compensate the sensorineural hearing loss by driving middle ear structures (e.g., the ossicles). These devices are successfully used in round window (RW) stimulation clinically, although this was initially not the intended use. Here, a novel microactuator, specifically designed for RW stimulation, was tested in human temporal bones to determine actuator performance and applicability. Methods . Stapes footplate response to RW stimulation was determined experimentally in human temporal bones and the obtained sound pressure output level was estimated. Results . The actuator had a flat displacement response between 0.125 and 4 kHz, a resonance between 4 and 7 kHz, and a roll-off above. At increasing contact force, the stapes footplate displacement decreased by 5–10 dB re μ m for forces ≥ 2 mN. The equivalent sound pressure level between 0.125 and 4 kHz amounted to 87–97 eq dB SPL and increased to 117 eq dB SPL for frequencies of 4–7 kHz. The total harmonic distortion (THD) of the actuator ranged within 15–40% for static forces of 5 mN. Conclusion . The feasibility of an electromagnetic actuator that may be placed into the RW niche was demonstrated but requires further optimization in terms of THD and static force sensitivity.